42 Ireland versus Poland away, what's the score? risk prediction using score charts for immigrants from high risk european countries in an Irish setting. (7th October 2015) - Tobin, L; Gibson, I; O'Hare, Daniel; Kiernan, T; Flaherty, G
Abstract : Introduction: Deaths due to cardiovascular disease (CVD) number 4 million annually in Europe with significantly higher mortality rates seen in Central and Eastern Europe. Large numbers of citizens from these regions migrated to Ireland in the last decade with those of Polish nationality now comprising the largest minority ethnic group in the country. The health status of these immigrants and the potential impact of migration on national CVD risk levels has not been studied. There is no guidance from the European Society of Cardiology (ESC) to date as to which SCORE chart to use in the case of an individual from a high risk country who has immigrated to a low risk nation. Methods: Immigrant adults over 18 years and from any of the high risk countries of Europe (according to the SCORE risk estimation tool) were recruited via convenience sampling in Limerick city. Screening was offered in occupational and community settings; a non-fasting lipid profile, blood pressure (BP) measurements, subjective questioning regarding physical activity levels, alcohol consumption and smoking status. The SCORE risk tool and relative risk categorisation were used to calculate CVD risk. Results: 81 participants (mean age 41 years) took part in this study. The majority were Polish (n = 72, 89%) and 54% (n = 44) were male. Subjects were divided into two groups for data analysis; those aged ≥40 years (n = 38, 46.9%, mean age 52 years) and younger subjects (n = 43, 53.1%, mean age 30 years). Very high levels of hypertension (55%) and hypercholesterolaemia (61%) were observed in those aged ≥40 years and 42% (n = 16) of the older subjects displayed a high or very high ten-year risk of death due to CVD. SCORE was strongly correlated with age (r = 0.70, p < 0.01); however it did not show any relationship with smoking, total cholesterol or systolic BP. When a comparison was made between the low and high risk charts for those aged ≥40 years, considerable differences were noted in risk categorisation. There was a twenty-fold increase in classification into the high or very high risk categories when the high risk chart was used. Conclusions: This study demonstrates that CVD risks inherent in a high risk population are preserved following immigration into a low risk area. As no current guidance exists from the ESC, the authors feel this cohort of people should undergo targeted risk factor modification in line with recommendations for high risk individuals. We have highlighted a deficiency in the SCORE risk charts, and feel further work is required to accurately assess the disease burden in this unique patient group.